2019
DOI: 10.1002/ece3.5261
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring program design for data‐limited marine biogenic habitats: A structured approach

Abstract: Marine biogenic habitats—habitats created by living organisms—provide essential ecosystem functions and services, such as physical structuring, nutrient cycling, biodiversity support, and increases in primary, secondary, and tertiary production. With the growing trend toward ecosystem approaches to marine conservation and fisheries management, there is greater emphasis on rigorously designed habitat monitoring programs. However, such programs are challenging to design for data‐limited habitats for which underl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 94 publications
(130 reference statements)
0
9
0
Order By: Relevance
“…This makes it more difficult to detect all taxa in areas of live sponge cover when compared to less structurally complex locations. Extractive sampling methods are generally not advisable (Loh et al, 2019) given that reef-building sponges are extremely fragile and slow to recover from physical disturbance (Kahn et al, 2016). Consequently, our community data are likely incomplete, especially in high sponge cover reefs.…”
Section: Discussionmentioning
confidence: 99%
“…This makes it more difficult to detect all taxa in areas of live sponge cover when compared to less structurally complex locations. Extractive sampling methods are generally not advisable (Loh et al, 2019) given that reef-building sponges are extremely fragile and slow to recover from physical disturbance (Kahn et al, 2016). Consequently, our community data are likely incomplete, especially in high sponge cover reefs.…”
Section: Discussionmentioning
confidence: 99%
“…This indicates that at the time of this study, two-thirds of the MPA case studies showed an inconsistent use of appropriate MPA-scale indicators and an inadequate assessment of the state of the benthos. This mismatch opposes the generally accepted opinion that good-quality initial data leads to good-quality monitoring and assessment (Loh et al, 2019). This possibly results from the slow application of assessment and monitoring programmes or from fewer resources being applied to the implementation phases in the majority of the MPA case studies.…”
mentioning
confidence: 87%
“…Effective monitoring and assessment programmes for MPAs require accurate baseline data, which first includes a characterization of the habitat, identifying key species of interest and major ecological relationships, and determines the ecological scale of the patterns or processes of interest (at a fine scale, broad scale, or both) (Buhl-Mortensen et al, 2017;Loh, Archer, & Dunham, 2019). Also, these baseline data should inform the long-term design of the monitoring and assessment programme for the MPA and should highlight any knowledge gaps.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations